Salpingoskopija - diagnostična metoda za ugotavljanje patoloških sprememb v jajcevodu - Virant-Klun, Irma (Zdravniški vestnik, 2003)
Background. To confirm the hypothesis that the incidence of pathological changes of the mucosa in the contralateral tube is higher in women with tubal pregnancy than in fertile women. To evaluate a new method for direct assessment of the tubal mucosa, salpingoscopy. Patients and methods. In the prospective study we enrolled 58 women in the period June 1998 - April 2002. The study group consisted of 23 women with tubal pregnancy and 19 infertile women seeking diagnostic laparoscopy. The exclusion criteria was tubal pregnancy that occurred in spite of an inserted intrauterine device or after an in vitro fertilization embryo transfer (IVF-ET). The control group consisted of 16 fertile women. Laparoscopy was performed in all the enrolled women. Peritubal adhesions were diagnosed laparoscopically, whereas intratubaladhesions were diagnosed by salpingoscopic examination of the ampullary tubal mucosa. Results. Laparoscopy revealed peritubal adhesions in 37 women: in 43% of women with a history of ectopic pregnancy, in 94% of infertile women, and in 19% of fertile women. On salpingoscopy pathologic changes of the ampullary tubal mucosa were most frequent in infertile women (47.7%) less frequent in women with a history of ectopic pregnancy (26.1%), and the least frequent in fertile women (63%). Pearson correlation coefficientyielded a weak correlation between the extensiveness of laparoscopically assessed lesions and salpingoscopically assessed pathology. None of the 23 women with pathologic changes of the ampullary tubal mucosa conceived spontaneously, whereas 43.5% of women with healthy tubal mucosa on salpingoscopy conceived spontaneously. The women with diagnosed pathologic changes of the tubal mucosa were referred forI IVF treatment to prevent further ectopic pregnancies. (Abstract truncated at 2000 characters)
Keywords: diagnostika; Fertilization In Vitro; Histerosalpingografija; human pregnancy; Hysterosalpingography; in vitro fertilization; Infertility, Female; neplodnost; Neplodnost ženska; nosečnost; Nosečnost izvenmaternična; Nosečnost jajcevodna; Oploditev in vitro; Pregnancy, Ectopic; Pregnancy, Tubal; zunajmaternična nosečnost